Diving into social innovation: A bibliometric analysis - Tânia Martins; Alexandra Braga; Marisa R. Ferreira; Vitor Braga (Administrative Sciences, 2022)
This paper aims to map and analyze the scientific production of social innovation, resulting in a contribution to the literature review and guidelines for future research. A bibliometric analysis was conducted to explore the trends on the topic. The primary objectives are (1) to identify how the literature defines the concept of social innovation and to track its evolution; (2) to measure productivity and identify key authors and scientific journals with the highest impact in the field and the association networks between their respective institutions and countries of origin; (3) to analyze and map citations, co-citations, and research topics to pinpoint the topics and dimensions related to social innovation in order to propose future research. Our paper clarifies the concept of social innovation, reports the progresses achieved within this research field, and measures the productivity on this specific topic.
Keywords: 350; social innovation; bibliometric analysis; co-citation analysis